2009
DOI: 10.1080/15412550902905961
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation Therapy for α1Antitrypsin Deficiency: A Meta-Analysis

Abstract: This meta-analysis supports the conclusion that augmentation can slow lung function decline in patients with AAT deficiency Patients with moderate obstruction are most likely to benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 56 publications
1
106
0
8
Order By: Relevance
“…However, recent results do suggest that augmentation therapy may have beneficial effects including reducing the frequency of lung infections and reducing the rate of decline of lung function. Several non-randomized observational studies and one meta analysis on the clinical effectiveness of AAT augmentation treatment showed a favorable result regarding lung function (FEV 1 ) in AAT-deficient COPD patients with moderate disease undergoing augmentation therapy (Chapman et al, 2009;Stockley et al, 2009). Clinical studies provide evidence that augmentation therapy with AAT reduces the incidence of lung infections in patients with AAT deficiency-related emphysema and reduces levels of the chemoattractant leukotriene B4.…”
Section: Augmentation Therapy With Aat In Patientsmentioning
confidence: 99%
“…However, recent results do suggest that augmentation therapy may have beneficial effects including reducing the frequency of lung infections and reducing the rate of decline of lung function. Several non-randomized observational studies and one meta analysis on the clinical effectiveness of AAT augmentation treatment showed a favorable result regarding lung function (FEV 1 ) in AAT-deficient COPD patients with moderate disease undergoing augmentation therapy (Chapman et al, 2009;Stockley et al, 2009). Clinical studies provide evidence that augmentation therapy with AAT reduces the incidence of lung infections in patients with AAT deficiency-related emphysema and reduces levels of the chemoattractant leukotriene B4.…”
Section: Augmentation Therapy With Aat In Patientsmentioning
confidence: 99%
“…At present, this treatment is available in a number of European countries and the United States (Chapman et al 2009). Some AATD individuals may be candidates for AAT replacement therapy; however, the efficacy of this treatment remains controversial (McCarthy and Dimitrov 2010).…”
Section: Replacement Therapymentioning
confidence: 99%
“…Well-designed and adequately powered randomized trials have been limited to date. A recent meta-analysis of published human studies demonstrated augmentation therapy does r e d u c e t h e a n n u a l r a t e o f l u n g f u n c t i o n d e c l i n e ( a s m e a s u r e d b y F E V 1 ) in A1ATD individuals (Chapman et al, 2009). …”
Section: Treatmentmentioning
confidence: 99%